2020
DOI: 10.1002/2211-5463.12779
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride ameliorates cognition dysfunction induced by sevoflurane anesthesia in rats

Abstract: Postoperative cognitive dysfunction is a common complication in elderly patients after surgeries involving anesthesia, but the underlying mechanisms are poorly understood. Lithium is a conventional treatment for bipolar disorder, which exerts a neuroprotective role in various diseases by inhibiting glycogen synthase kinase‐3β (GSK‐3β) in the brain and spinal cord. However, it is not known whether lithium chloride (LiCl) can protect against cognitive dysfunction induced by sevoflurane (SEV) anesthesia. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In contrast, all of these gene expressions reduced significantly in LiCl treated cells. Similar results were also observed in the study of the antiviral effects of LiCl on coxsackie virus [26] and Sendai virus [27]. This result suggests that the anti-viral effect of LiCl on MDV might not depend on the expression of interferon and interferon-related factors.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, all of these gene expressions reduced significantly in LiCl treated cells. Similar results were also observed in the study of the antiviral effects of LiCl on coxsackie virus [26] and Sendai virus [27]. This result suggests that the anti-viral effect of LiCl on MDV might not depend on the expression of interferon and interferon-related factors.…”
Section: Discussionsupporting
confidence: 87%
“…It is interesting to note that we found a significant increase in NLGN clusters upon lithium treatment despite plasma levels falling just below the clinically relevant therapeutic range. It is tempting to speculate that the synaptogenic effects of Li do not underlie the improvement in the core BD symptoms of mania and depression, which are the main clinical measures to assess treatment efficacy in BD, but rather contribute to some therapeutic benefit of Li that is less well established such as reducing cognitive decline 65 . However, more work is needed to understand the exact implications of these results for the effect of treatment in BD.…”
Section: Implications For Human Studiesmentioning
confidence: 99%
“…Because anaesthetic choice can be effectively managed by anaesthesiologists, it is important to determine the role of anaesthetic choice in POCD. Propofol and sevoflurane are common general anaesthetics used in clinical anaesthesia, and animal experiments have also shown that propofol and sevoflurane can cause the occurrence of POCD ( 15 , 16 ). The choice of anaesthetic may affect cognitive outcome after the operation, but the results from clinical research have always been contradictory.…”
Section: Introductionmentioning
confidence: 99%